Web-Based Mail Administration Information System At The Legal Bureau Of Southeast Sulawesi Secretariat - Eviriawan; Statiswaty*; Isnawaty; Hikma; Devy Natalia Nurtiani (Jurnal Riset Informatika, 2025)
The administration of correspondence is an important element in the governance of government organizations, but its manual management often causes various problems such as delays in distribution, difficulty in searching for archives, and lack of transparency. This research aims to design and develop digital information applications for online mail administration management as a solution to increase productivity, speed, and accuracy in the process of handling official documents within the Legal Bureau of the Regional Secretariat of Southeast Sulawesi Province. The development method applied is Agile with the Scrum framework approach. The application was built using the PHP programming language based on the Laravel framework. The testing process is carried out using the black box testing method to ensure that each feature in the application functions as expected. The development results show that this application is able to handle incoming and outgoing mail directly, perform the disposition process, search for archives, and manage users efficiently. The system is also considered valid based on testing basic functions, interface, security, and navigation. Thus, this information system can be a digital solution that supports the improvement of efficiency and transparency of correspondence administration in the government environment.